Adrenal venous sampling as used in a patient with primary pigmented nodular adrenocortical disease - Peng, Xiaoxin; Yu, Yintao; Ding, Yi; Yang, Fang; Chen, Xiangshu; Chang, Cheng (Translational Cancer Research; Vol 6, No 6 (December 28, 2017): Translational Cancer Research, 2017)
Background: Primary pigmented nodular adrenocortical disease (PPNAD) is a rare cause for hypercortisolism, and it diagnosis is highly challenging as the symptoms are often mild and the patients usually visit doctors long after the onset of their symptoms. Methods: Present herein is a rare case of PPNAD which was diagnosed thanks to adrenal venous sampling. A 21-year-old woman presented with centripetalism lumbodynia, hypertension, osteoporosis, and amenorrhea. Plasma cortisol concentrations were elevated, and there was a loss of circadian rhythms. Laboratory reports indicated her plasma adrenocorticotropic hormone (ACTH) as normal and brain imaging showed no delayed enhancement in the saddle region of the pituitary gland, confirming a diagnosis of ACTH-independent Cushing’s syndrome. Enhancement CT scan showed tiny nodules on her left adrenal gland. Adrenal venous sampling (AVS) discoverer elevated plasma cortisol in left adrenal vein and the left part of the inferior vena cava mesial side, indicating increased cortisol secretion in the left adrenal. Results: Following an adrenalectomy taken on her left adrenal, immunohistochemistry revealed PPNAD on the left adrenal. Conclusions: Adrenal venous sampling contributes to the diagnosis of PPNAD and that of Cushing’s syndrome as well. Adrenal venous sampling, an effective diagnostic of PPNAD, proves useful in diagnosis of Cushing’s syndrome.